Inside out & back again - Lai, Thanhha (New York Scholastic, 2011)
Through a series of poems, a young girl chronicles the life-changing year of 1975, when she, her mother, and her brothers leave Vietnam and resettle in Alabama.
Keywords: Novels in verse; Vietnamese Americans -- Fiction; Emigration and immigration -- Fiction; Immigrants -- Fiction; Vietnam -- History -- 1971-1980 -- Fiction; Alabama -- History -- 1951- -- Fiction